1997
DOI: 10.1073/pnas.94.7.3010
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-mediated inhibition of the epithelial brush border Na + /H + exchanger, NHE3, requires an associated regulatory protein

Abstract: NHE3 is the Na + /H + exchanger located on the intestinal and renal brush border membrane, where it functions in transepithelial Na + absorption. The brush border Na + absorptive process is acutely inhibited by activation of cAMP-dependent protein kinase, but the molecular mechanism of this inhibitory effect is poorly understood. We have identified two regulatory proteins, E3KARP and NHERF, that interact with NHE3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
459
3
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(478 citation statements)
references
References 35 publications
11
459
3
4
Order By: Relevance
“…LPA 2 has carboxyl-terminal motifs that allow interaction with a PDZ (PSD-95/DlgA/ZO-1) domain of the Na + /H + exchanger regulatory factor 2 (NHERF2), which functions as a scaffold to link signaling proteins, such as PKA and PKCα, to GPCRs and transporters at the cell surface [21,23,[29][30][31]. NHERF2 links LPA 2 to PLC-β3 and hence affects the activation of downstream targets, such as Erk and cyclooxygenase-2 [23].…”
Section: Protection Of Caco-2 From Etoposide-induced Apoptosis Is Depmentioning
confidence: 99%
“…LPA 2 has carboxyl-terminal motifs that allow interaction with a PDZ (PSD-95/DlgA/ZO-1) domain of the Na + /H + exchanger regulatory factor 2 (NHERF2), which functions as a scaffold to link signaling proteins, such as PKA and PKCα, to GPCRs and transporters at the cell surface [21,23,[29][30][31]. NHERF2 links LPA 2 to PLC-β3 and hence affects the activation of downstream targets, such as Erk and cyclooxygenase-2 [23].…”
Section: Protection Of Caco-2 From Etoposide-induced Apoptosis Is Depmentioning
confidence: 99%
“…cAMPdriven inhibition of NHE3 can be mediated via NHERF1, NHERF2, and NHERF3 (PDZK1), whereas cGMP-mediated inhibition was found to specifically require NHERF2. 28,57 NO was found to inhibit NHE3 function by the NO-cGMP pathway, but without account for the effect of inducible NO under inflammation conditions for NHE3 regulation. 40,58 In another study, NHE3 expression was found to be unaltered in cytokine-induced inflammation in interleukin-10edeficient mice marked by up-regulated iNOS levels.…”
Section: Cftr-inos Signaling Complexmentioning
confidence: 95%
“…54e56 It is interesting that the same intracellular cAMP, Ca 2þ , or cGMP that activates CFTR would inhibit NHE3. 55,57 Not only do CFTR and NHE3 share the same secondary messengers for regulation but also regulatory scaffolding NHERF proteins. 48 NHE3 harbors a C-terminal PDZ-binding motif, similar to CFTR that would mediate NHE3 interaction with other membrane proteins, cytoskeleton, and protein kinases through NHERFs.…”
Section: Cftr-inos Signaling Complexmentioning
confidence: 99%
“…NHERFs also serve to recruit signaling molecules, such as PKA, PKC, and PI-3 kinase, to the receptor complexes (Fanning and Anderson 1999;Shenolikar and Weinman 2001;Yun 2003;Shenolikar et al 2004;Lee-Kwon et al 2005;Weinman et al 2005). Importantly, although NHERF-1 and NHERF-2 were originally described in the kidney, Northern blot analysis shows an overlapping and wide-spread distribution pattern for NHERF-1 and NHERF-2 mRNAs in human tissues, including brain, heart, colon, small intestine, liver, prostate, spleen, and placenta (Weinman et al 1995;Yun et al 1997). Immunohistochemical studies have demonstrated NHERF-1 and NHERF-2 in the human (Weinman et al 2002) and mouse (Wade et al 2003) kidney, NHERF-1 in the mouse retina (Nawrot et al 2004) and Schwann cell processes (Gatto et al 2003), and NHERF-2 in endothelia and pericytes from rat descending vasa recta (Lee-Kwon et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…NHERF-1 (also called EBP50) was the first scaffold identified for an epithelial transporter and was found to mediate protein kinase A (PKA) inhibition of NHE3 in renal brush border vesicles (Weinman et al 1995). Subsequently, its close relative NHERF-2 (also called E3KARP) was cloned and characterized (Yun et al 1997). NHERF-1 and NHERF-2 consist of 358 and 337 amino acids, respectively, sharing 54% homology and possess two PDZ domains and a C-terminal ezrin-radixin-moesinmerlin (ERM)-binding domain that can interact with the actin cytoskeleton (Fanning and Anderson 1999;Shenolikar and Weinman 2001;Wade et al 2003;Yun 2003;Shenolikar et al 2004).…”
Section: Introductionmentioning
confidence: 99%